Дочки-матери на выживание: [роман] / Юлия Лавряшина - Лавряшина Юлия Александровна (Э, 2017)
Экземпляры: ф.16 (2018) / Инвентарный номер: 54830 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л137 / ББК: 84(2=411.2)6-44